Antibiotic resistance of Helicobacter pylori isolated from patients in Nanjing, China: A cross-section study from 2018 to 2021 - Jiang, Zongdan; Qian, Xuetian; Wang, Zhi; Dong, Yunfan; Pan, Yuqin; Zhang, Zhenyu; Wang, Shukui (Frontiers in Cellular and Infection Microbiology, 2022)
The increasing antibiotic resistance of Helicobacter pylori infection is a globally urging problem. To investigate the H. pylori resistance situation in Nanjing, China, we enrolled patients in Nanjing First Hospital from January 2018 to May 2021. H. pylori strains were isolated from patients who had at least one positive 13C-urea breath or rapid urease result. Subsequently, we performed antibiotic susceptibility tests on the isolated strains to clarithromycin, metronidazole, levofloxacin, amoxicillin, furazolidone and tetracycline. ARMS-PCR was conducted to determine H. pylori clarithromycin resistance gene mutation. Our results demonstrated that the primary resistance rates of metronidazole, clarithromycin, levofloxacin, amoxicillin, furazolidone and tetracycline were 67.19% (1417/2109), 35.99% (759/2109), 24.23% (511/2109), 0.76% (16/2109), 0.28% (6/2109) and 0.09% (2/2109), respectively. The resistance rates of metronidazole, clarithromycin and levofloxacin elevated significantly after treatment and the three antibiotics composed the majority of multi-resistance patterns. However, the resistance rates of amoxicillin, furazolidone and tetracycline were still in low levels after treatment. ARMS-PCR showed a rather good consistency with antibiotic susceptibility test in detecting clarithromycin resistance, with a kappa value of 0.79. Overall, this study revealed the latest complex situation of antibiotic resistance of H. pylori infection in Nanjing and offered suggestions on clinical medication for curing H. pylori.